EKSISTENSI WARALABA (FRANCHISE) MENURUT PERATURAN PEMERINTAH NO. 42 TAHUN 2007 SEBAGAI PERJANJIAN INNOMINAAT - Asuan, Asuan (Solusi, 2017)
This research with normative juridical method. The juridical approach is the approach to the problem by looking in terms of the prevailing laws and regulations regarding the law of the treaty, the existence of Franchise (franchise) according to Government Regulation no. 42 of 2007 as an Innominaat Agreement ". Normative is an approach that uses secondary data with the preparation of a conceptual framework. Normative research is conducted to obtain legal materials in the form of theories, concepts and legal principles derived from the literature in the form of Laws, Government Regulations, Civil Code and the literature-literature, lecture materials and other sources related to problems. By using legal materials such as primary legal materials, secondary legal materials and tertiary legal materials. Result of research: franchise agreement is one of agreement form which involves franchisor as franchisor, franchisee who accept franchise, and Department of Industry and Trade fostering franchise industry. This legal relationship creates rights and obligations that are binding on the franchisor and franchisee. The franchise agreement includes an unnamed agreement (innominat agreement) governed outside the Civil Code. In violation of the franchise agreement the dispute settlement can be done through a court (lawsuit), a musyawara and or through an arbitration body regulated by Law of the Republic of Indonesia Number 30 Year 1999 on Alternative Dispute Settlement and Arbitration. While the legal sanction in violation of franchise agreement is regulated in Article 16 of Government Regulation Number 42 Year 2007 where legal sanction in the form of administrative sanction is done through 3 (three) stages, giving written warning, fine and / or revocation of registration letter of franchise.